Eco-anxiety, climate concern, and fatalistic outlooks: Insights from U.S. crisis text conversations on climate distress - Jennifer D. Runkle; Kelsey Herbst; Sophie Ryan; Kelly Sewell; Ashley Mallare; Ian Berry; Emma Getz; Arden McKee; Martie P. Thompson; Margaret M. Sugg (The Journal of Climate Change and Health)
Introduction: Ecologic anxiety and climate distress describe psychological and emotional responses to the uncertain future of our planet amid climate change. Crisis hotlines and text-based counseling services may address mental health concerns linked to climate anxiety, yet limited research explores these responses through digital crisis text lines. This study presents results from a qualitative thematic analysis of U.S. crisis text conversations mentioning climate change by exploring emotional responses and coping resources commonly discussed. Methods: We analyzed anonymized text data from Crisis Text Line (CTL), a free, U.S.-based digital crisis platform with over nine million conversations since 2017, focusing on a sample of texts mentioning ''climate change.” A comprehensive codebook was developed, incorporating predetermined and emergent codes for climate change exposures, crisis flags, emotional responses, and special topics. Using a structured, iterative thematic analysis approach that combined deductive and inductive methods, the study identified and categorized emerging themes. Results: A total of 337 text transcripts were analyzed. Texters displayed significant emotional responses to climate change, grouped into three categories: Eco-anxious, General Climate Concern, and Fatalistic Future Outlook. Findings reveal the tangible impacts of extreme weather, the exacerbating role of media coverage, and the interaction between climate change and other life stressors. Texters used various coping strategies for climate-related distress, including social support, creative and nature-based activities, positive information, and professional resources like CTL. Counselor-recommended techniques, such as grounding exercises and journaling, also helped manage emotional well-being. Conclusions: Themes underscore the complex nature of texters' emotional and psychological responses, varied coping mechanisms, and how climate concerns can inspire proactive environmental actions. The analysis highlights the urgent need for targeted support interventions, particularly for those with a fatalistic outlook, to address mental health challenges related intensifying climate events.